Multiline observations of S255IR with ALMA. Issue Volume 13:Issue S332(2017) (4th September 2018) - Zinchenko, Igor; Liu, Sheng-Yuan; Su, Yu-Nung; Zemlyanukha, Petr
Abstract: We present preliminary results of the high resolution (0.10″ × 0.15″) observations of the high mass star forming region S255IR with ALMA in several spectral windows from ∼335 GHz to ∼350 GHz. The main target lines were C 34 S(7–6), CH3 CN(19 K − 18 K ), CO(3–2) and SiO(8–7), however many other lines of various molecules have been detected, too. We present sample spectra and maps, discuss briefly the source structure and kinematics. A new, never predicted methanol maser line has been discovered.